L’abbaye de Lisle-en-Barrois (Meuse) : opportunités et contraintes spatiales d’un temporel cistercien frontalier - Christophe Wissenberg (Bulletin du Centre d’Études Médiévales d’Auxerre)
Although Lisle-en-Barrois abbey, a former short-lived canonical foundation, now profits by an edition of its 12th century charters, its spatial approach gaps have led to a re-examination of the corpus and, above all, its extension to the entire voluminous cartulary. By focusing on the content of the titles – primary source of information – and cross-referencing it with environment and available cartographic sources, the toponymic survey has made it possible to reduce the unknowns to a negligible proportion, a necessary condition for the spatio-temporal analysis that is the subject of this research. The development of the middle-important granges network shows the initial episcopal steering and some seized opportunities in this border area, but also the perspectives canalised by a lively monastic competition, particularly Benedictine, which finally led to a bipolar temporal. At the turn of the thirteenth century, the abbey classically went beyond its initial circle of restrictions – by moving into the towns – and diversified its supplies (wine and salt) and income (rents), embarking on a process of adaptation – if not abandonment – of its principles in line with seigniorial economy, of which the founding of the villeneuve of Deuxnouds is the most eloquent incarnation.